Salix glauca shrub-ring carbon isotopes - Patrick Sullivan (Arctic Data Center, 2016)
Carbon isotope discrimination in alpha-cellulose of Salix glauca growth rings. Measurements were made in support of Cassandra Gamm's M.S. thesis at the University of Alaska Anchorage. The goal was to examine potential increases in moisture limitation of shrub growth over time.